Adult age differences in prospective memory in the laboratory: are they related to higher stress levels in the elderly? - Ihle, Andreas; Kliegel, Matthias; Hering, Alexandra; Ballhausen, Nicola; Lagner, Prune; Benusch, Julia; Cichon, Anja; Zergiebel, Annekathrin; Oris, Michel; Schnitzspahn, Katharina M. (Frontiers in Human Neuroscience, 2014)
To explain age deficits found in laboratory-based prospective memory (PM) tasks, it has recently been suggested that the testing situation per se may be more stressful for older adults, thereby impairing their performance. To test this assumption, subjective and physiological stress levels were assessed at several times during the experiment in 33 younger and 29 older adults. In addition, half of participants were randomized in a condition where they completed a relaxation intervention before performing a time-based PM task. Results confirmed the age deficit in laboratory PM. Subjective and physiological stress levels showed no age difference and no detrimental association with PM. The intervention successfully reduced stress levels in both age groups but had no effect on PM or the age deficit. In conclusion, data suggest that age deficits usually observed in laboratory PM may not be due to higher stress levels in the older adults.